Hubungan kualitas tidur dengan pola makan mahasiswa - Fildzah Badzlina; Mega Puspa Sari (ARGIPA (Arsip Gizi dan Pangan), 2022)
College students are prone to have poor sleep quality. This can cause eating disorders in students which can increase the incidence of obesity. The purpose of this study was to determine the relationship between student sleep quality and eating habits as a preventative measure to increase the incidence of obesity. This study was an observational quantitative study with a cross-sectional approach. The subjects of this study were 107 students of the University of Muhammadiyah Prof. DR. Hamka (UHAMKA) with purposive sampling technique. Sleep quality data was taken using the Pittsburgh Sleep Quality Index (PSQI) questionnaire using the google form which was distributed to all students of the UHAMKA in September 2021. The data analysis carried out was the Man Whitney Test because the data were not normally distributed. The results showed that there was a significant relationship between sleep quality and fast food consumption habits. However, there is no relationship between sleep quality and fruit consumption, vegetable consumption, and consumption of sweetened foods and beverages. This study extends previous research regarding the relationship between poor sleep quality and the frequency of fast food consumption in college students.